Effect of Cooking Methods on Quality Characteristics of Nuggets and Patties from Sheep, Goat and Rabbit Meat - Sen, A.R.; Karim, S.A. (Journal of Meat Science, 2011)
The effect of cooking methods (moist vs dry heat) on physicochemical and sensory attributes of sheep, goat and rabbit meat products was studied. The cooking yield % was significantly (P<0.05) higher in nuggets (moist heat cooking) than patties (dry heat cooking) in all three species. The nuggets contained more (P<0.05) moisture and less fat than patties. The cooking method did not significantly influence the sensory attributes of sheep and goat meat products. Tenderness and juiciness scores were higher (P<0.05) in nuggets of rabbit meat as compared to patties. The results indicated that yield characteristics of nuggets prepared by moist heat method were better than patties prepared by dry heat. Further, it was concluded that irrespective of species, nuggets rated superior than patties in sensory attributes.